2012
DOI: 10.5796/electrochemistry.80.214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scratching of Coating Surface on the Electrochemical Behavior of PVD Al-Mg-Si Coated Steel

Abstract: Effect of scratching of coating surface on the electrochemical behavior of PVD Al-Mg-Si coated steel has been investigated using an open circuit potential (OCP), anodic polarization and galvanic couple test. The OCP monitoring showed a fast ennoblement of OCP then attained a steady state value during the last stage of monitoring. There were two types of corrosion products of scratched coating that protected from continuous corrosion and act as selfhealing. The first is passive film that arises from the adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…10 The microstructure of hot dipped Zn coating is composed of a single-phase microstructure. The analysis of hot dipped indicated that the coating surface consisted of two principle phase in its microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…10 The microstructure of hot dipped Zn coating is composed of a single-phase microstructure. The analysis of hot dipped indicated that the coating surface consisted of two principle phase in its microstructure.…”
Section: Methodsmentioning
confidence: 99%